Zinc Oxide, a UV light active photocatalyst for the degradation of anionic dye - Gaire , Deepak; Rajbhandari Nyachhyon, Armila (Scientific World, 2025)
Zinc oxide, a UV-light active photocatalyst has been successfully synthesized in laboratory by co-precipitation method. The ZnAC2.2H2O and NaOH were used as precursor materials. The EDTA was used as a capping agent to confine the size and to control the over-growth of the photocatalyst. Characterization of as prepared photocatalyst was done by X-Ray Diffraction and Fourier Transform Infrared Spectroscopy. The peak at 32.2° (100), 35.0° (002), 36.6° (101), 47.8° (102), 57.0° (110), 63.2° (103), 68.2° (200), and 69.4° (112) at 2θ degrees indicated the crystalline phase of as prepared material and average crystalline size was calculated by Debye-Scherer equation and was found to be 17.81 nm. The FTIR spectra showed the clear bands of Zn-O, C-H, and O-H at 400 to 600 cm-1, 1650 cm-1 and 3350 cm-1 respectively. Then, as synthesized ZnO material was used as catalyst to degrade anionic dye: methyl orange (MO), under UV light irradiation. The results revealed that ZnO showed an excellent photocatalytical performance at pH 7, and an optimum catalyst dose of 0.1 g per 100 mL of 10 mg/L dye concentration. The 81.20% MO dye degredation was observed within 5 hrs. The removal efficiency of MO dye was found to be increased significantly up to 89 % when oxidant H2O2 was added. It may be due to scavenging effect of H2O2 oxidant. It also helps to reduce recombination of electron- hole pair during photocatalytic application. The degradation followed the pseudo first-order kinetics with rate constant k = 0.5507 also signifies the efficiency of ZnO. Hence, an economical and environment-friendly ZnO photocatalyst can be prepared and used to degrade anionic dye from the wastewater contaminated with synthetic azo dyes.